2015
DOI: 10.1136/bmj.h3855
|View full text |Cite
|
Sign up to set email alerts
|

Doctors and medical students in India should stop wearing white coats

Abstract: Evidence shows that long sleeved coats facilitate the transmission of infection in hospitals, leading to avoidable harm and cost to patients, says Edmond Fernandes Although emphasis on evidence based medicine is increasing, we still selectively tackle issues that we like and collectively ignore the ones that we don't-such as doctors wearing white coats.Historically, long sleeved coats, popularly called aprons, were worn by laboratory scientists. But in the 19th century, after scientists showed that many doctor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…10 This is also a burning topic in India as recently an article has been published by Dr. Edmond Fernandes, in which he questions the need to wear white coats, stating that in India's tropical climate white coats should be discouraged and an easy way to reduce hospital acquired infection by India's Ministry of Health would be to ban doctors and students white coat. 8 Previous studies have revealed that white coats do harbour bacteria. 1,3,6,7,9,[11][12][13][14] This contamination has ranged from 28.46% to 95%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 This is also a burning topic in India as recently an article has been published by Dr. Edmond Fernandes, in which he questions the need to wear white coats, stating that in India's tropical climate white coats should be discouraged and an easy way to reduce hospital acquired infection by India's Ministry of Health would be to ban doctors and students white coat. 8 Previous studies have revealed that white coats do harbour bacteria. 1,3,6,7,9,[11][12][13][14] This contamination has ranged from 28.46% to 95%.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for wearing are similar to other studies. 1,7,8 The location of white coat use is hospital only (44.4%) followed by patient interactions (20.7%) and always (19.9%). Always indicates that the white coat is worn in clinical as well as nonclinical areas.…”
mentioning
confidence: 99%
“…This is true as coats washed after a week were equally contaminated. To decrease contamination, white coats should be washed within a week with disinfectants 8 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this may become contaminated with bacteria and play a role in dispersion of nosocomial infections to the patients. An important microorganism in this regard is methicillin-resistant Staphylococcus aureus (MRSA) which is antibiotic resistant and increases mortality 8 . In September 2007 the bare below the elbow policy brought about instatement in England.…”
Section: Introductionmentioning
confidence: 99%
“…To protect their street clothes from contamination, medical and laboratory professionals wear a knee length over coat which is known as white coat 2 . It is a symbol of professionalism, identification 3 , trust and respect from others, where white color indicates purity and goodness 1,[3][4][5][6][7] . In many medical institutions "White Coat Ceremony" is conducted to welcome MBBS students to the medical field 8,9 .…”
Section: Introductionmentioning
confidence: 99%